Effect of Modeling Techniques with Behavioral Counseling lesson Through Study to Improve Attitudes Able to Logical Thinking, Funny and Reason - Ni WayanWitari; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
This study aims to improve the attitude of being able to think logically, funny and reason. The study population was 72 students, and the research sample was 36 students, With a kind of quasi-experimental, pretest-posttest control group design. Judging from the analysis tcount 3,347 > ttable 1,690 so H0 is rejected and Haaccepted. So, there are significant differences in the that states are able to think logically, funny, and reason, before and after using the theory of behavioral counseling by modeling techniques. Behavioral counseling can be inferred through the lesson study modeling technique is effective to improve the attitude of being able to think logically, funny and reason.